2006
DOI: 10.1029/2005jd006086
|View full text |Cite
|
Sign up to set email alerts
|

Apportionment of black carbon in the South Shetland Islands, Antarctic Peninsula

Abstract: [1] Simultaneous time series measurements of black carbon (BC), aerosol particle number (ANC), radon, and SEM-EDS analysis for total carbon were collected at the Brazilian Antarctic station Ferraz, northwest of the Antarctic Peninsula (62°05 0 S, 58°23.5 0 W) for the years of 1993, 1997, and 1998. A new data screening technique was applied in an effort to distinguish long-range from local contaminations of BC. Analyses of data revealed a small increase in BC concentration during winter-to-spring seasons. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 34 publications
(62 reference statements)
3
74
1
1
Order By: Relevance
“…Figure 7a presents a trajectory density plot derived from HYSPLIT back trajectories corresponding to high-radon concentrations (> 400 mBq m −3 ). While Pereira et al (2006) reported transport to Ferraz from as far north as Brazil (with radon > 2000 mBq m −3 ), KSG high-radon events in 2013 were typically the result of slow-moving air masses crossing South America between 47 and 55 • S. In terms of potential anthropogenic pollutant sources, this fetch region includes several population centres of small-to-intermediate size, including Punta Arenas (population ca. 123 000).…”
Section: Intermediate Events (Hourly Concentrations 100-400 Mbq M −3 );mentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 7a presents a trajectory density plot derived from HYSPLIT back trajectories corresponding to high-radon concentrations (> 400 mBq m −3 ). While Pereira et al (2006) reported transport to Ferraz from as far north as Brazil (with radon > 2000 mBq m −3 ), KSG high-radon events in 2013 were typically the result of slow-moving air masses crossing South America between 47 and 55 • S. In terms of potential anthropogenic pollutant sources, this fetch region includes several population centres of small-to-intermediate size, including Punta Arenas (population ca. 123 000).…”
Section: Intermediate Events (Hourly Concentrations 100-400 Mbq M −3 );mentioning
confidence: 99%
“…While numerous studies have already used radon to assist with the interpretation of trace species transported to, or produced within, the Antarctic atmosphere (Gros et al, 1998;Winkler, 1992;Murphey and Hogan, 1992;Wyputta, 1997;Pereira et al, 2004Pereira et al, , 2006, few of the published data sets have provided continuous, direct (i.e. not via progeny), long-term, highsensitivity radon observations, with hourly temporal resolution.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed: (1) they are three persistent dust sources in South America: the first one is located, farther north, in the Bolivian Altiplano (19 -20°S, 67-68°W), and the two others are located in central Patagonia (Argentina), roughly encompassed by [37 -45°S, 66-70°W] and by [27 -34°S, 67 -70°W]. Preferential dust mobilization is observed from September to February [Prospero et al, 2002], when the cloud cover vanishes and aridity increases [Paruelo et al, 1998;Diaz et al, 2006]; (2) although the main wind direction at 45°S is westward over Patagonia, calm events occur mostly in winter but also in summer, a southerly component is evident in summer [Paruelo et al, 1998], and occasional strong wind events from Eastern sector occur throughout the year over semi-arid areas of central east Patagonia [$11% of major wind events, Labraga, 1994]; (3) Meridional transport of black carbon from tropical burning areas in Brazil to the northern Antarctic Peninsula has also been evidenced and related to intermittent mechanism involving the low-level jets east of Andes, the displacement eastward of frontal systems passing over Drake Passage and the high pressure over the Atlantic Ocean associated with the subtropical height [Pereira et al, 2006]. Andean summital areas are on the boarder of such southward flow.…”
Section: Calcium Seasonal Cycles Countingmentioning
confidence: 99%